Pengaruh Ukuran, Profitabilitas, Leverage dan Kinerja Lingkungan terhadap Environmental Disclosure dan Kinerja Keuangan Perusahaan Pertambangan di Indonesia - Noegroho, Fajar; Susilowati, Endah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The environmental issues caused by the mining industry are often attributed to the lack of environmental information disclosure by mining companies. This leads to a decrease in public and investor trust. Consequently, many mining industries suffer financially due to declining profits and investment levels. Therefore, there is a need for companies to enhance public trust through environmental information disclosure, as well as other factors such as company size, profitability, leverage, and environmental performance, which are considered potential reasons for mining companies to engage in environmental information disclosure. This research adopts a quantitative approach. The population of the study consists of mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The sampling technique employed is purposive sampling, resulting in 49 companies that meet the criteria, with a total of 195 data points. The data in this study were analyzed using Partial Least Square (PLS). The findings of this research indicate that only the variable of Company Size has a significant positive influence on Environmental Disclosure, while the variables of Leverage and Profitability have a significant positive impact on Financial Performance. These results suggest that there are still many mining companies that prioritize business interests over environmental concerns. Keywords: Firm Size, Profitability, Leverage, Environmental Performance, Environmental Disclosure, Financial Performance